Sex differences in stress-modulated cocaine vulnerability: female rodents are more sensitive to the effects of stress exposure at different developmental stages - Martínez-Caballero, María Ángeles; Calpe-López, Claudia; García-Pardo, Maria Pilar; Arenas, M. Carmen; Manzanedo, Carmen; Aguilar, María A. (Frontiers in Behavioral Neuroscience, 2025)
IntroductionStressful life events can trigger the initiation of cocaine use, facilitate the transition to a cocaine-use disorder (CUD), and precipitate relapse. Evidence suggests that women progress more rapidly to a CUD than men. Thus, the influence of stressful life events on CUD development may differ by sex, contributing to the enhanced vulnerability seen among females. In this work, we provide a comprehensive (non-systematic) review of clinical and preclinical studies comparing the effects of cocaine and its modulation by stress in both sexes.MethodsWe performed a search of the PubMed database (1986–2025) in which we combined the keywords “cocaine” and “stress” with “sex differences” or “female rat” or “female mice” or “women.” We then read the abstracts of the search results to select potentially relevant studies, which we read in full to determine if they fulfilled our criteria and to extract the relevant information.ResultsSex is often overlooked as a biological variable in preclinical and clinical research. The results of clinical studies indicate the existence of sex differences in the response to stress among individuals with CUD. Preclinical studies strongly suggest that female rodents are more vulnerable to developing addiction-like features than male rodents, particularly in the self-administration paradigm. Furthermore, exposure to stress appears to amplify the effects of cocaine, especially in females.DiscussionThere is growing evidence that women and female rodents are more vulnerable to the behavioral and neurochemical changes that characterize cocaine addiction. The influence of sex should be considered in research and in the selection of strategies for preventing and treating CUD, including those targeting stress reduction.